Teknologi Tepat Guna UMKM Kotim Simulasi Harga Komputer Rakitan Menggunakan Sistem Pendukung Keputusan - Sri Wahyuni; Slamet Riyadi (Journal of Computer System and Informatics (JoSYC), 2020)
Assembled computers are computers that are self-assembled or can be assembled by stores with specifications accordance with the user's request. Apart from that, the difficulty of choosing components of a computer device that fits with your needs and financial budget is not an easy thing. So, there needs to be a supporting application in order to make it easier for users to choose computer peripheral components. The selection of assembled computer devices is using the fuzzy mamdani method, which is a suitable method to converting languages that are difficult for the public to understand, because the fuzzy database itself is a database that has queries that contain a fuzzy variable.